2011
DOI: 10.1002/chem.201101425
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Functionalization of Liposomes with the gH625 Peptide from Herpes simplex Virus Type I for Intracellular Drug Delivery

Abstract: Liposomes externally modified with the nineteen residues gH625 peptide, previously identified as a membrane-perturbing domain in the gH glycoprotein of Herpes simplex virus type I, have been prepared in order to improve the intracellular uptake of an encapsulated drug. An easy and versatile synthetic strategy, based on click chemistry, has been used to bind, in a controlled way, several copies of the hydrophobic gH625 peptide on the external surface of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPG)-based lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 44 publications
(28 reference statements)
1
69
0
Order By: Relevance
“…Then, the film was hydrated by addition of 0.1 M phosphate buffer 0.9% wt NaCl at pH 7.4, sonicated, and extruded through a polycarbonate membrane with 100 nm pore size. The real number of functional azido groups, exposed on the liposomal surface, was checked using a fluorescent derivative (7-nitrobenzofurazan-propargylglycine) as previously described by Tarallo et al 28 As expected, ~50% of the theoretical azido groups were available on the outer liposomal surface for the click-chemistry reaction. One, two, or four copies of P6.1 peptide were bound on the monomeric, dimeric, or tetrameric azido scaffold to obtain Lipo-M6, Lipo-D6, and Lipo-T6 liposomes (Figure 2).…”
Section: Liposome Formulation and Characterizationmentioning
confidence: 99%
“…Then, the film was hydrated by addition of 0.1 M phosphate buffer 0.9% wt NaCl at pH 7.4, sonicated, and extruded through a polycarbonate membrane with 100 nm pore size. The real number of functional azido groups, exposed on the liposomal surface, was checked using a fluorescent derivative (7-nitrobenzofurazan-propargylglycine) as previously described by Tarallo et al 28 As expected, ~50% of the theoretical azido groups were available on the outer liposomal surface for the click-chemistry reaction. One, two, or four copies of P6.1 peptide were bound on the monomeric, dimeric, or tetrameric azido scaffold to obtain Lipo-M6, Lipo-D6, and Lipo-T6 liposomes (Figure 2).…”
Section: Liposome Formulation and Characterizationmentioning
confidence: 99%
“…10,11 This peptide has proved to exhibit exceptional vector properties 9 and has been shown to be essentially internalized by a nonendocytic pathway avoiding endosomal entrapment. 7,[12][13][14][15][16][17] In recent studies, it was also shown to be able to cross the blood-brain barrier in vitro and in vivo. 18 gH625 is, therefore, a very good delivery vector 9 and its coupling to NPs may be exploited to change their internalization mechanism and in case of MNPs, to avoid or reduce their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of advanced technologies for peptide identification and modification further supports the extensive application of peptides in the field of theranostics research. 31,32 We have previously demonstrated that gH625, a 19-residue peptide, is a membrane-perturbing domain 13 that interacts with model membranes, contributing to their merging 13 and is able to traverse the membrane bilayer and transport a cargo (quantum dots, liposomes, and dendrimers) 16,18,20 into the cytoplasm and across an in vitro model of the BBB. 19 Uptake studies suggested a nonactive translocation mechanism in crossing the lipid bilayer, which may vary depending on the cargo.…”
Section: Discussionmentioning
confidence: 99%
“…15 Further, gH625 has been used extensively for vector-mediated strategies that enable passage of a large variety of small molecules as well as proteins across cell membranes in vitro. [16][17][18][19][20] Conjugation of gH625 to the surface of nanoparticles also enhances their transport across the BBB, as previously demonstrated in an in vitro model of the BBB. 19 Whether or not multifunctional nanodevices, designed and tested in vitro, work properly in vivo in a mammalian host is still not fully understood.…”
mentioning
confidence: 98%